Warriors Who Do Not Kill in War: A Buddhist Interpretation of the Warrior’s Role in Relation to the Precept against Killing - Sugiki, Tsunehiko (Religions, 2020)
Buddhist scriptures in ancient South Asia include discourses that teach measures by which a warrior can face problems in confrontation with foreign armies and domestic rebel troops without resorting to killing them in battle. These moderate measures have not attracted much attention in previous studies on Buddhist statecraft and warfare. There are eleven kinds, and they can be organized according to the following three types: retreat from the role of warrior, resolution without pitched battle, and fighting in a pitched battle without killing. Similar ideas regarding measures for resolving military confrontations can be found in Indian Classics in the context of statecraft. The compilers of the Buddhist discourses collected ideas about similar measures from common sources and reshaped those borrowed ideas from the perspective of the Buddhist precept against killing. A warrior who implemented such measures did not acquire as much negative karmic potential as intentional killing produces. In premodern warrior societies, religion often provided the institutional basis for both a code of ethics and a soteriology for warriors, for whom fighting was in fulfillment of their social role. The compilation of discourses containing measures that do not involve killing represents an aspect of Buddhism’s function in ancient South Asia.